Developing Creative Thinking and Aesthetic Perception in National Visual Arts Education - Ismoilov Otabek Shavkat o‘g‘li (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines methods for enhancing students’ creative thinking and aesthetic perception in national visual arts education. It discusses the use of interactive lessons, project-based activities, and digital tools to develop students’ visual thinking, artistic perception, and engagement with traditional art forms. The study highlights the role of student-centered pedagogy and a supportive creative environment in fostering aesthetic awareness and encouraging originality.